Strategic Arms Restriction as a Factor of the Russian-American Relations in the XXI Century: Problems and Prospects - Pavel Borisovich Kartyshev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Article is devoted to the Russian-American relations in the context of disarmament policy, in particular, on reduction of nuclear arsenals of the parties. The author carries out the analysis of the main treaties from the point of view of real nuclear parity of Russia and the USA. Article opens the main problems in policy of disarmament, in particular, a problem of placement of the American system of antimissile defense in countries of Eastern Europe. The author gives expert estimates of efficiency of future missile defense system in Poland and the Czech Republic.